Social-emotional aspects of quality of life in multiple sclerosis. Issue 4 (21st April 2018) - Lex, Heidemarie; Weisenbach, Sara; Sloane, Jacob; Syed, Sana; Rasky, Eva; Freidl, Wolfgang
Abstract: Multiple sclerosis (MS) is an inflammatory auto-immune disease of the central nervous system. It leads to many impairments including physical, cognitive, psychological, and social challenges. Our study examined gender and cultural associations with quality of life (QoL), personal characteristics, and benefits from having MS among those with MS. The study was conducted in Austria and the United States. The sample included 128 participants, 64 in each country, of whom 78 were women and 50 were men aged between 20 and 57 years. We used standard statistical tests, including analyses of covariance (ANCOVA) and partial correlations for the analysis of quantitative data. For the qualitative part of the survey we used semi-structured interviews, which we transcribed and coded to identify categories in the answers for qualitative analyses. Austrian participants with MS perceived a higher social-emotional QoL in comparison to American participants. American participants expressed a higher self-esteem in comparison to Austrian participants. Men reported a lower ability to express love than women. Independent of sex/gender and nationality, participants reported benefits through the disease, especially with regard to improved compassion, mindfulness, improved family relations and lifestyle gains. The qualitative interviews revealed additional gender differences for coping with the illness; and in experiences, expectations, and challenges related to MS. These insights can be used to develop targeted psychological and social support interventions aimed toward improving social-emotional QoL for persons with MS.